Contextual Teaching and Learning (CTL) dalam Pembelajaran PAI - Abdi, Muhammad Iwan (IAIN Samarinda, 2011)
Contextual teaching learning (CTL) is an educational process that aims to help students see meaning in academic material they are learning by connecting academic subjects with the context of their daily, which is related to personal circumstances, social, and cultural development. In Contextual teaching and learning (CTL) takes an approach that is more empowering students with the expectations of students able to construct knowledge in their minds, rather than memorizing facts. Besides, students learn through experience rather than memorize, given knowledge of the facts and not a concept readily accepted but something that must be constructed by the students. To achieve this goal include the eight components of the system, the following: making meaningful connections, doing meaningful work, conduct self-regulated learning, collaborate, think critically and creatively, helping individuals to grow and develop, achieving high standards , and using authentic assessment. In learning PAI, CTL developed by focusing on moral or affective touch protege acquired through personal experience that photographing their daily environment. This touch your heart and thoughts will inspire students to practice it.